If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -27 = 2x + 33 Reorder the terms: -27 + 8x = 2x + 33 Reorder the terms: -27 + 8x = 33 + 2x Solving -27 + 8x = 33 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -27 + 8x + -2x = 33 + 2x + -2x Combine like terms: 8x + -2x = 6x -27 + 6x = 33 + 2x + -2x Combine like terms: 2x + -2x = 0 -27 + 6x = 33 + 0 -27 + 6x = 33 Add '27' to each side of the equation. -27 + 27 + 6x = 33 + 27 Combine like terms: -27 + 27 = 0 0 + 6x = 33 + 27 6x = 33 + 27 Combine like terms: 33 + 27 = 60 6x = 60 Divide each side by '6'. x = 10 Simplifying x = 10
| 8c+1b=12.89 | | 2v-v=12-v | | 8x-31=19+3x | | 4x-3(x-2)=27 | | x^2+x^4=90 | | -4x-8(3-5x)=192 | | 12xz^2+36x^2z-120x^3=0 | | 7r^2+10r+3=0 | | 1+5p=-4+6p | | 25x^2+40x+80=0 | | x+3x-1+.5x+13=57 | | -8x-7=10-9x | | 15x^2+34x-6=0 | | 3x=12z | | (8+w)54=5 | | 7-n=1-4n | | d+d+2d= | | -3(-4-6)+7(-x+5)=-8 | | 5x-69=74-8x | | -9+2n=-n | | 9x-110=66-7x | | .60(x-19)=-15 | | 8x+24=20 | | 3(x-10)+3(2-5)=5x-3 | | 6f+10=60 | | 3x=5x+11 | | 12x-3-7x+8=11(-1-5x)-4(-4+6x) | | 1=5(t-6) | | -x-54=-7x+54 | | X+2+x+2+x+2+X+2=12 | | 1+x+4+x+7+x+10=0 | | 0.02(n-550)=105 |